Antibiotics and usage areas - Topal, Murat; Şenel, Gülşad Uslu; Topal, E.Işıl Arslan; Öbek, Erdal (Erciyes Üniversitesi, 2015)
Antibiotics those supress growth of microorganisms or kill them are very effective bioactive materials which have biological origin or synthetically obtained. There are many antibiotics according to the effect manner of them and the microorganisms they effect. Antibiotics are used for human and animal health, food protection in food industry, health and growth of aquatic livings as fish and in hospitals and scientific activities in pharmaceutical industry. Antibiotics are the widely used pharmaceuticals in whole world. Antibiotics are used wrongly and excessively in developing countries. Furthermore, antibiotics could be sold in pharmacies even in markets without prescription. It should be born in mind that antibiotic usage has damages together with benefits. Therefore, required cautions have to be taken for the decrement of antibiotic consumption in our country.

Mikroorganizmaların büyümesini durduran ya da öldüren antibiyotikler, biyolojik kaynaklı ya da sentetik olarak elde edilen çok etkili biyoaktif maddelerdir. Etki tarzlarına ve etkiledikleri mikroorganizmalara göre çok sayıda antibiyotik bulunmaktadır. Antibiyotikler insan ve hayvan sağlığı, gıda sektöründe besinlerin korunması, balık gibi sucul canlıların sağlığı ve büyümesi ve hastanelerde ve ilaç endüstrisinde bilimsel araştırma faaliyetleri için kullanılmaktadır. Antibiyotikler tüm dünyada en çok kullanılan ilaçlardır. Antibiyotikler, gelişmekte olan ülkelerde yanlış ve aşırı kullanılmaktadır. Ayrıca, antibiyotikler reçetesiz olarak eczanelerde, hatta marketlerde dahi satılabilmektedir. Antibiyotik kullanımının yararları olmasının yanısıra zararlarının da olduğu akılda tutulmalıdır. Bu nedenle ülkemizde antibiyotik tüketiminin azaltılması için gerekli önlemlerin alınmalıdır.
Antibiyotikler ve kullanım alanları